Comparative study on the effectiveness of corticosteroid injections between trigger fingers with and without proximal interphalangeal joint flexion contracture. (February 2016) - Shinomiya, R.; Sunagawa, T.; Nakashima, Y.; Kawanishi, Y.; Masuda, T.; Ochi, M.
Trigger fingers with proximal interphalangeal joint flexion contracture are suggested to have a poorer response to corticosteroid injection than those without contracture, though this has not been proven scientifically. We compared the clinical response to corticosteroid injection between trigger fingers with and without proximal interphalangeal joint contracture, and investigated the influence of the injection on the A1 pulley and flexor digitorum tendons using ultrasonography. One month after injection, pain was significantly reduced in the no contracture group, and 56% of trigger fingers with proximal interphalangeal joint contracture resolved. Before injection, relative thickening of the A1 pulley and flexor digitorum tendons, and a partial hypoechoic lesion of the flexor digitorum superficialis tendon were observed in the contracture group. One month after injection, the thickening of the tendons and the A1 pulley was reduced, but the partial hypoechoic lesion was still observed in significant numbers. We have demonstrated that the presence of a proximal interphalangeal joint contracture was associated with a reduced clinical response to corticosteroid injection, and we suggest that the pathologic change in the flexor digitorum superficialis tendon, represented by the partial hypoechoic lesion, contributed to corticosteroid injection resistance. Level of evidence: IV